CURRICULUM DESIGN FOR DEVELOPING 21ST-CENTURY SKILLS: A CASE STUDY OF AN ISLAMIC HIGH SCHOOL - Dewi Sinta; Agus Fakhruddin; Abid Nurhuda; Nur Muhammad Lathif (Research in Education and Rehabilitation)
Education in the 21st century requires a curriculum responsive to students' needs in developing skills relevant to the times. This study aims to explore the curriculum design for 21st-century skills development in an Islamic high school in West Bandung Regency, Indonesia. The selection of this school as the research subject is based on its curriculum development, which allegedly equips students with several skills, including 21st-century skills. This study employed a qualitative approach with a case study design. Data was collected through observation, interviews, and document analysis. Data analysis techniques included reduction, display, verification, and conclusion drawing. The results indicate that this school implements a combined (parallel) curriculum design combining the Emancipated Curriculum, Typical School Curriculum, Cambridge Curriculum, and Islamic Boarding Curriculum integrated with the Child-Friendly School, Adiwiyata School, and Disaster Safe Education Unit programs. This curriculum design places much emphasis on project-based learning, the use of digital media, lots of religious material, environmental awareness movements, and habituation activities. The application of this curriculum design plays a vital role in developing 21st-century skills in terms of competitiveness, piousness, leadership, management, critical thinking, creativity, problem-solving, collaboration, communication, foreign language skills, digital literacy, entrepreneurship, caring attitude, environment, and awareness of sustainable lifestyle. This finding implies the importance of adopting a holistic approach in curriculum design to develop students prepared to face the demands of the modern world. The study contributes insights into best practices in curriculum design for developing 21st-century skills in senior high schools.